Hydrogen bonding effects on the reactivity of [X-Fe(III)–O–Fe(IV)=O] (X = OH, F) complexes towards C–H bond cleavage - Xue, Genqiang (2013)
Complexes 1-OH and 1-F are related complexes that share similar [X–Fe(III)–O–Fe(IV)=O](3+) core structures with a total spin S of ½, which arises from antiferromagnetic coupling of an S = 5/2 Fe(III)-X site and an S = 2 Fe(IV)=O site. EXAFS analysis shows that 1-F has a nearly linear Fe(III)–O–Fe(IV) core compared to that of 1-OH, which has an Fe–O–Fe angle of ~130° due to the presence of a hydrogen bond between the hydroxo and oxo groups. Both complexes are at least a thousand-fold more reactive at C–H bond cleavage than 2, a related complex with a [OH–Fe(IV)–O–Fe(IV)=O](4+) core having individual S = 1 Fe(IV) units. Interestingly, 1-F is tenfold more reactive than 1-OH. This raises an interesting question about what gives rise to the reactivity difference. DFT calculations comparing 1-OH and 1-F strongly suggest that the H-bond in 1-OH does not significantly change the electrophilicity of the reactive Fe(IV)=O unit and that the lower reactivity of 1-OH arises from the additional activation barrier required to break its H-bond in the course of H-atom transfer by the oxoiron(IV) moiety.